Enterprise performance and macroeconomic control - BUITER, W.; LAGO, R.; STERN, N. (PSL Quarterly Review, 2013)
The work argues that poor macroeconomic control is an important cause of poor enterprise performance. The authors review the empirical evidence on the relationship between macroeconomic stability and the performance of the real economy both at the aggregate and the project levels, before presenting a cursory review of the theoretical links. The importance of implementing microeconomic and structural reforms alongside the establishment of macroeconomic stability is also dealt with. The authors conclude with suggestions for policy makers regarding the priorities in the development of the institutions required to achieve and preserve a stable macroeconomic framework. JEL Codes: E20